Cross-border migration and travel: A virtuous relationship - Jacques Poot (IZA World of Labor, 2015)
The ongoing relationships between emigrants and their families, friends, and business contacts in their home countries can increase outbound and inbound cross-border travel, while cross-border tourism and business and study trips can trigger migration. New communication technologies, such as social media and video chat, only partially substitute for face-to-face meetings. In fact, the greater use of such technologies boosts demand for in-person meetings. Short- and long-term cross-border movements are becoming more complex, creating challenges for measuring immigration and for defining target populations for legislation and public policy.
Keywords: F22; J1; R1; 330; cross-border mobility; visiting friends and relatives; business travel; networks; information and communications technology